2020
DOI: 10.3390/molecules25040974
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Mesoporous Organosilica Nanoparticles with BOC Group, towards HIFU Responsive Agents

Abstract: Periodic Mesoporous Organosilica Nanoparticles (PMONPs) are nanoparticles of high interest for nanomedicine applications. These nanoparticles are not composed of silica (SiO2). They belong to hybrid organic–inorganic systems. We considered using these nanoparticles for CO2 release as a contrast agent for High Intensity Focused Ultrasounds (HIFU). Three molecules (P1–P3) possessing two to four triethoxysilyl groups were synthesized through click chemistry. These molecules possess a tert-butoxycarbonyl (BOC) gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…Taking into attention the well-described affinity of trialkoxysilanes to form condensed derivatives (e.g., nanostructured materials and catalysts ), a similar approach was chosen for the self-assembly of the target Cu­(II)-CLMS: alkaline (NaOH in ethanol) hydrolytic condensation of PhSi­(OMe) 3 , followed by an exchange reaction with CuCl 2 and complexation with ethylenediamine. Different reaction media were tested for the subsequent crystallization procedures (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Taking into attention the well-described affinity of trialkoxysilanes to form condensed derivatives (e.g., nanostructured materials and catalysts ), a similar approach was chosen for the self-assembly of the target Cu­(II)-CLMS: alkaline (NaOH in ethanol) hydrolytic condensation of PhSi­(OMe) 3 , followed by an exchange reaction with CuCl 2 and complexation with ethylenediamine. Different reaction media were tested for the subsequent crystallization procedures (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Durand et al reported the synthesis and characterization of framework-functionalized mesoporous silica nanoparticles with the aim of CO 2 release which acted as a contrast agent for high intensity focused ultrasounds (HIFU) [13]. In this study, several multi-silylated precursors containing tert-butoxycarbonyl (BOC) group were synthesized.…”
Section: Health and Biomedical Applicationsmentioning
confidence: 99%
“…The 13 C-CP-MAS solid state NMR spectra (Les Ullis, France), the BET surface areas (Mérignac, France), Dynamic Light Scattering (DLS, Pessac, France) and Zeta potential values (Orsay, France) were obtained from equipments of University of Montpellier [39]. The 1 H-and 13 C-NMR spectroscopy (Bruker Biospin, Rheinstetten, Germany), Mass-Spectrometry (MS, Bruker Biosciences Española, Madrid, Spain), elemental analysis, Infra-Red spectroscopy (IR, Bruker Biosciences Española, Madrid, Spain), Powder X-Ray diffraction (P-XRD, Almelo, Netherlands) and Transmission Electron Microscopy (TEM, JEOL Ltd., Akishima, Tokyo, Japan) were performed at the Universitat Autònoma de Barcelona (UAB) [39].…”
Section: General Remarksmentioning
confidence: 99%
“…The samples were then extracted with a solution of NH 4 NO 3 (6 g/L in 96% EtOH) for three times and washed successively with 96% ethanol, Mili-Q water, 96% ethanol. The E-Pn PMO NPs were obtained as white solids [39]. E-P1 90/10 PMO NPs: 13…”
Section: Synthesis Of P2mentioning
confidence: 99%
See 1 more Smart Citation